2022
DOI: 10.1111/hequ.12415
|View full text |Cite
|
Sign up to set email alerts
|

Graduating in uncertain times: The impact of COVID‐19 on recent graduate career prospects, trajectories and outcomes

Abstract: This article examines the impacts of the COVID‐19 pandemic on recent UK graduates' initial employment outcomes and how they experience the transition into a challenging labour market context. We draw on longitudinal survey and interview data, collected from recent graduates who had mainly graduated during the onset of the COVID‐19 pandemic in summer 2020 that examines graduate perception of the labour market, impacts on labour market entry impacts and early career progression and effects of periods of unemploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Changes in the workplace prompted by the pandemic, such as increased reliance on remote work and short-term freelance jobs (Lund et al, 2021; Tomlinson et al, 2023), may have altered students’ views about the value of a college education (Flores, 2021; Lederman, 2021; Tough, 2023). To help students see the value in what they are learning, instructors need to draw deliberate connections between coursework and employable skills (Davidson, 2017; Naufel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the workplace prompted by the pandemic, such as increased reliance on remote work and short-term freelance jobs (Lund et al, 2021; Tomlinson et al, 2023), may have altered students’ views about the value of a college education (Flores, 2021; Lederman, 2021; Tough, 2023). To help students see the value in what they are learning, instructors need to draw deliberate connections between coursework and employable skills (Davidson, 2017; Naufel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to teaching, graduate students juggle multiple responsibilities including coursework and research (Park & Ramos, 2002) and must navigate their dual identities as staff members and students (Slack & Pownall, 2023). Like the undergraduates in their courses, graduate students face an uncertain job market (Bayerlein et al, 2021; Flaherty, 2020; Lund et al, 2021; Tomlinson et al, 2023), which might make them more mindful of the importance of broad-based employable skills.…”
Section: Why Teach Employable Skills?mentioning
confidence: 99%
“…Our findings regarding the overall improved engineering persistence mid-COVID-19 interruptions were consistent with our prior study . Some plausible explanations include the attention of the two universities on retention efforts, changes to grading policies, a weaker job market during COVID-19, stimulus initiatives, families' emotional and financial support during COVID-19 interruptions, and student sense of purpose during the pandemic Cao et al, 2020;Eloff, 2021;Gelles et al, 2020;Murty & Payne, 2021;Nadya & Pustika, 2021;Núñez, 2022;Sharma & Yukhymenko-Lescroart, 2022;Tomlinson et al, 2022). Although the abrupt transition to online learning was far from perfect, some studies have indicated students appreciated the flexibility it afforded (Salhab, 2022;Serhan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…7 Studies have provided evidence for single countries, notably higher inactivity rates and an increase in the number of young people not in employment, education or training in Italy 8 ; job losses of low-wage earners working in industries most affected by the lockdown in Canada 17 ; and the scarring and labour market disorientation of young people in the UK. 18 Researchers also note the sociodemographic divides of labour market outcomes, such as the fall in the employment of Hispanic and young people in the US. 19 However, it can be said that the pandemic exacerbated the persistent employment problems of the graduate labour market.…”
Section: Graduates In the Hostile Labour Market: Visible And Invisibl...mentioning
confidence: 99%
“…The impacts of the pandemic on the labour market outcomes worldwide include skill mismatch, job losses, temporary employment, underemployment, reduced job opportunities, salary cuts, health issues, and the renewed relevance of vocational education 7 . Studies have provided evidence for single countries, notably higher inactivity rates and an increase in the number of young people not in employment, education or training in Italy 8 ; job losses of low‐wage earners working in industries most affected by the lockdown in Canada 17 ; and the scarring and labour market disorientation of young people in the UK 18 . Researchers also note the sociodemographic divides of labour market outcomes, such as the fall in the employment of Hispanic and young people in the US 19 .…”
Section: Graduates In the Hostile Labour Market: Visible And Invisibl...mentioning
confidence: 99%